Minne, translated: embodying liturgy, love, and trauma in the Diepenveen sister-book and the Facons revelations - Perk, GG (University of Oxford, 2022)
This article traces pandemic trauma in two understudied Middle Dutch texts produced by Devotio Moderna communities of Augustinian canonesses regular, a sister-book from Diepenveen (eastern Low Countries) and a visionary text from Facons (Antwerp). In both texts, members of the community succumb to the plague. Allowing medieval trauma to interrogate modern trauma theory, this discussion participates in feminist enquiries about wounds as instruments of control and responds to medievalist critiques of asceticism. It first considers how translation of the liturgy –into the vernacular and into bodies– intervenes in trauma, before examining how trauma, in turn, intervenes in the liturgy, and mapping how trauma inflects mutual charity and enclosure, which the texts prescribe as protection against the plague. Finally, this essay scrutinizes how trauma cloisters the sisters in painful charity with one another, but also uncovers how these psychic wounds open up sites of agency within irredeemable suffering.